A participação do auxiliar em saúde bucal na equipe de saúde e o ambiente odontológico - Costa, Adriana Oliveira [UNESP]; Silva, Ligia Prandi da [UNESP]; Saliba, Orlando; Garbin, Artênio José Isper [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (FapUNIFESP (SciELO), 2012)
Introduction: The formation of Oral Health Team, healthy and ergonomic work conditions influence on quality of dental attendance to patient. Objective: In this observational and cross-sectional study, it was observed the participation of the dental assistants (ASB) on dental team on public health, to verify the items related to health legislation, the existence and distribution of equipment in dental offices. Material and method: The data collection was performed using questionnaires and observations on locals for consultation. It were interviewed 75 dentists from 9 cities of Health Regional Department (DRS) – XV – São José do Rio Preto City and it was evaluated 34 dental offices. Result: Of total 75 dentists, 21 (28%) worked alone and among them, 6 (29%) worked at school and 15(71%) at Health Basic Unit (UBS). From 34 dental offices, 2 (6%) did not show any equipment for sterilization and among those that had it, the autoclave was the most used method (44%). Among the analyzed dental offices, 31 (91%) had dustbin for common waste and 23 (68%) of contaminated waste was inadequate. It was noted that 13 (38%) did not have local to wash de hands; in 23 (68%) there was paper towel; in 20 (59%) there was ideal soap dishes, and the compressor was installed into dental offices in 5 (15%) of local for attendance. In relation to dental offices adequacy for the help work, all of them (n = 19) were dissatisfied. Conclusion: The existence of ASB was present in the Centers of Dental Specialties (CEO) and Units of Family Health due legal exigencies and it were found inadequate healthy and ergonomic conditions, suggesting the necessity of reorganization of w

Introdução: A composição da equipe de saúde bucal e as condições sanitárias e ergonômicas no ambiente de trabalho influenciam na qualidade do atendimento odontológico prestado ao paciente. Objetivo: Neste estudo observacional e transversal, objetivou-se verificar a participação do auxiliar na equipe odontológica do serviço público, bem como os itens relacionados com a legislação sanitária e a existência e a distribuição dos equipamentos no consultório. Material e método: A coleta de dados foi realizada por meio de aplicação de questionários e observações nos locais de atendimento. Foram entrevistados 75 cirurgiões-dentistas de nove municípios do DRS XV – São José do Rio Preto-SP e avaliados 34 consultórios. Resultado: Do total de 75 cirurgiões-dentistas, 21  (28%) trabalhavam sozinhos, sendo seis (29%) em escolas e 15 (71%) em UBS. Dos 34 consultórios, dois (6%) não apresentavam qualquer equipamento de esterilização e, dos que possuíam, a autoclave era o meio mais utilizado, em número de 15 (44%). Dos consultórios analisados, 13 (38%) não possuíam lixeiras do lixo comum e, em 18 (53%), as existentes eram inadequadas. Quanto ao lixo contaminado, em 21 (62%), as lixeiras eram inadequadas e, em dois (6%), ausentes. Ou seja: em apenas 11 (32%), as lixeiras para este tipo de lixo eram adequadas. Notou-se ainda que 13 (38%) não tinham lavatórios para mãos; em 23 (68%), havia toalheiro de papel; em 20 (59%), saboneteiras adequadas, e o compressor estava instalado dentro dos consultórios em cinco (15%) dos locais de atendimento. Quanto à adequação  dos consultórios para o trabalho auxiliado, todos (n = 19) estavam insatisfatórios. Conclusão:  A  existência do ASB apresentou-se principalmente nos CEOs e nas Unidades de Saúde da Família por exigência legal e foram encontradas condições sanitárias e ergonômicas inadequadas, sugerindo a necessidade de reorganização no processo de trabalho e de gestão.
The dental assistant participation in the public health team and the dental environment
Keywords: Human resources; Public health; Dental assistants; Recursos humanos; Saúde pública; Assistentes de Odontologia